DEFINITION OPTIMAL MASS SORBENT “ECOLAN” FOR CLEANING WATER FROM OIL PRODUCTS - Матвєєва, О.Л.; Демянко, Д.О.; Огданська, І.О. (Proceedings of National Aviation University (archive), 2012)
The article deals with cleaning water from oil products sorbent “Ecolan”. Efficiency of research cleaning oil water sorbent. Identify the optimum mass sorbent, which will be rational to use this sorbent, as well as the minimum time of interaction sorbent “Ecolan” and contaminated water. On the basis of anticipated study assessment the effect of efficiency sorbent “Ecolan” physical and chemical conditions holding the process of cleaning.